Development of Financial Market Activity by Optimization of Stock Issuance - Fayziyev Jahongir; Samiyev Sardor Iskandarovich (European Science Publishing, 2023)
What is the relationship between markets and development? It is argued that markets promote growth, and that growth in turn encourages the formation of markets. Two models with endogenous market formation are presented to analyze this issue. The first examines the role that financial markets - banks and stock markets - play in allocating funds to the highest valued use in the economic system. It is shown that intermediation will arise under weak conditions. The second focuses on the role that markets play in supporting specialization in economic activity. The consequences of perfect competition in market formation are highlighted.
Keywords: development of financial market, market activity, stock issuance, financial markets, economy.